Gestión de seguridad y salud ocupacional y el desempeño laboral en el Hospital Militar Santa Rosa, Iquitos 2020 - Silva Wong, Katherine Patricia (2021)
The general objective of this research was to determine the relation ship between occupational health and safety management and job performance at Hospital Militar Santa Rosa, Iquitos 2020; opting for a descriptive-correlational research and non-experimental design, for which a sample of 63 workers from said institution has been taken, who were survey ed through a question naire and an observation guide that analyzes their perception regarding the variables evaluated; managing to conclude that the management of occupational health and safety is deficient, since therelation ships between colleagues and bosses are not the best, like wise, the institution does not have monitoring and survei llance systems both external and internal, it also almost never establishes working conditions that minimize the risk of illness and injury. Ont heother hand, it was determined that the level of job performance in the 2020 periodis low, the internal disciplinary regulations are not complied with correctly by the workers, and the results achieved are almost never adequate, since not the problems presented in institution are almost never resolved affecting the achievement of institutional goals. Finally, it was determined that there is a statistic all significant correlation of 0.000 between occupational health / safety management and job performance at the Santa Rosa de Iquitos Military Hospital in 2020, it is also considered that the relationship is positive and considerable of 0.816.